Pengaruh Edukasi Kesehatan Berbasis Flipbook Digital terhadap Tingkat Pengetahuan Anemia pada Ibu Hamil - Haninggar, Rizki Dyah; Anwar, Yulianti; Ashriady, Ashriady (Yayasan Mandar Indonesia, 2025)
The high prevalence of anemia among pregnant women remains a major public health problem that adversely affects maternal and neonatal health, particularly in areas with limited access to health information. Innovative digital-based educational media are needed to improve pregnant women’s understanding of anemia effectively. This study aimed to analyze the effect of digital flipbook-based health education on changes in anemia knowledge among pregnant women. This study employed a quasi-experimental one-group pre-test and post-test design conducted at Binanga and Bambu Primary Health Centers, Mamuju Regency, from May to December 2025. A total of 34 pregnant women were selected using purposive sampling based on predetermined inclusion and exclusion criteria. Anemia knowledge was assessed using a structured questionnaire consisting of 12 questions administered before the intervention and two weeks after digital flipbook-based education. Data analysis was performed using the Paired Samples t-Test after confirming normal data distribution. The results showed that the mean anemia knowledge score increased from 9.44 ± 1.56 before the intervention to 10.76 ± 1.13 after the intervention. A statistically significant difference was observed between pre-test and post-test knowledge scores (t = 5.656; p < 0.001), with a mean difference of 1.32 points. Digital flipbook-based health education was proven effective in improving anemia knowledge among pregnant women and can be recommended as an alternative educational medium in maternal health services.